Impact of physical activity on adolescents with anxiety disorders and depression : a systematic review (2024)
The aim of this study was to conduct a systematic review of the existing scientific literature on the impact of physical activity on adolescents with anxiety disorders and depression. The scientific literature was reviewed following the PRISMA guidelines in the Web of Science, PubMed, ScienceDirect and Refseek databases. The keywords used were: “Physical Activity”, adolescents”, associated with the words ‘anxiety and depression’. The sample consisted of 24 scientific articles, which met the inclusion criteria. The most significant results showed that the constant practice of physical activity benefits the mental health of adolescents, reducing anxiety and depression, and improving their mood and ability to adapt to different daily situations. Physical activity helps to modify the way adolescents view their emotional problems, acting as an antidepressant by positively impacting the central nervous system and promoting personal acceptance.